Comparison of two advanced anaerobic digestions of sewage sludge with high-temperature thermal pretreatment and low-temperature thermal-alkaline pretreatment. (May 2020) - Xiao, Benyi; Tang, Xinyi; Yi, Hao; Dong, Lixin; Han, Yunping; Liu, Junxin
Graphical abstract: Highlights: Two advanced anaerobic digestions (AAD) of sewage sludge were compared. Two thermal pretreatments caused similar disintegration degree on sewage sludge. Two AAD had similar methane production and organic matter removals. Methanogenic pathways of two AAD were different. AAD with low-temperature thermal-alkaline pretreatment had a higher energy efficiency. Abstract: Semi-continuous experiments were conducted to compare the performances and energy efficiencies of two advanced anaerobic digestions (AAD) of sewage sludge with high-temperature thermal pretreatment (HTTP, 160 ± 1 °C and 0.55 MPa for 30 min) and low-temperature thermal-alkaline pretreatment (LTTAP, 60 ± 1 °C and pH 12.0 ± 0.1 for 30 min), which had similar sludge disintegration degree (9.44–9.48%). At the steady period of a SRT 20 d, the two AAD had similar methane production (150.22 ± 9.55 ml/L/d and 151.02 ± 12.56 ml/L/d) and organic matter removals (22.54 ± 2.84% and 23.15 ± 2.46% for volatile solids-VS). The results of high-throughput sequencing showed that the methanogenic pathways of the two AAD were strictly hydrogenotrophic (AAD with HTTP) and hydrogenotrophic/acetoclastic methanogenesis (AAD with LTTAP), respectively. The energy balance analysis suggested that the AAD with LTTAP was superior to that with HTTP because the former had a higher energy efficiency (1.610) than the latter (1.358).